2017
DOI: 10.2218/ijdc.v12i1.426
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Digital Preservation Challenges in Nigerian Libraries: Librarians' Perspectives

Abstract: This paper investigates digital preservation challenges in Nigerian libraries. In carrying out this study four research questions were posed. The study sample population comprised of 172 participants at the 2nd Conference of Certified Librarians from various libraries and institutions across Nigeria, organised by the Librarians’ Registration Council of Nigeria (LRCN) in Abuja on the 11th – 16th October, 2015. The outcome of the study revealed that digital preservation challenges persist despite the awareness o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Most (70%) of the 157 participants at the 2 nd conference of certified librarians registration council of Nigeria identified lack of policies as a major barrier in digital preservation activities at their institutions (Sambo et al, 2017). Majority (71.4%) of the 26 institutions in Botswana lacked retention rules.…”
Section: Resultsmentioning
confidence: 99%
“…Most (70%) of the 157 participants at the 2 nd conference of certified librarians registration council of Nigeria identified lack of policies as a major barrier in digital preservation activities at their institutions (Sambo et al, 2017). Majority (71.4%) of the 26 institutions in Botswana lacked retention rules.…”
Section: Resultsmentioning
confidence: 99%
“…Also, the findings of the study were in agreement with According to Jain and Mnjama (2016) who stated that preservation of digital records included the following problems and challenges: lack of knowledge, shortage of adequately trained personnel to handle digital records, insufficient funding for human and physical resources required to establish and maintain the programmes and the technological obsolescence and fragility of storage media. It is known that the long-term digital preservation of resources in the archives is the preferred strategy for curbing the decay of materials and addressing the problems of hardware, software obsolescence, and backup issues (Sambo et al 2017).…”
Section: Presentation Of Finding and Analysismentioning
confidence: 99%
“…Regrettably, 70% indicated that they have not had any digital preservation training and as a result, they were not equipped with relevant skills to appreciate the exercise. Three years after, the situation has not changed significantly as Sambo, Urhefe and Ejitagha [31] found that lack of training was second, behind hardware and software obsolesces, on the list of challenges confronting digital preservation programmes in Nigeria. Similar challenges have been observed in the Zimbabwean National Archives context [52].…”
Section: Digital Preservation Practices In University Librariesmentioning
confidence: 99%